Perbaikan Estimasi Loading Bagian Machinery PT. X - Rahardjo, Mikhael Ariesto; Felecia, Felecia (Jurnal Titra, 2015)
PT. X is a industrial machinery company who supply their products to other companies of PT. X parent company. PT. X is currently experiencing major problems in terms of overload capacity and loading estimates are less accurate. This study aims to resolve both of these issues, which can lower the actual loading and improve the accuracy of loading estimation. Repairs carried out by estimating the reduction in loading by reducing the categories of working hours of others. A decrease in working hours of others are able to lower the actual loading is estimated at 24.23% in 2014 and 19.64% in 2015. The real proposal given itself are focus on improvement in the design department. Estimates loading then also carried out after fixing the actual loading conditions. Estimates loading at PT. X itself are having a great error when compared with the actual loading of existing, which amounted to 62.84% in 2014. Improvements loading estimation is done by using optimized manhour quota where uncertainty weight is the most important thing to its result. The resulting error rate amounted to 32.23% for the project loading, 9:48% for the total loading, and 6.78% for the total loading with repairs.